Conocimiento materno sobre alimentación complementaria e influencia en el estado nutricional de lactantes de 6-24 meses que acuden al Centro de Salud tipo A Zamora - Pardo Sarango, Estefanía Alejandra (2022)
Complementary feeding is the food that begins to be offered to the infant from 6 months to 2 years; along with breastmilk. From this age, the supply of nutrients from milk is insufficient to cover all the requirements and this constitutes a transition path for the child to be integrated into the family diet. This study is descriptive correlational and cross-sectional type. The objective was to analyze maternal knowledge about complementary feeding and its influence on the nutritional status of infants from 6 to 24 months who attend the Type A Zamora Health Center. The population was represented by 45 mothers and their children between 6 and 24 months of age; a survey with 21 items was applied to the mothers to obtain their sociodemographic data and identify knowledge about complementary feeding. Thus, it was determined that 48.9% of the surveyed population has a medium level of knowledge, 42.2% low knowledge and only 8.9% high knowledge. The information about the children’s nutritional status was obtained from their Integral Health Book in which 66.7% of them have a normal nutritional status, but 33.4% of the children have poor nutrition; of which, 15.6% are chronically malnourished, 11.1% are overweight, and 6.7% are obese. On the other hand, the mothers’ level of knowledge has no relation with the child’s nutritional status